Cardiovascular events in patients with familial hypercholesterolemia and hyperlipoproteinaemia (a): Indications for lipoprotein apheresis in Poland. Issue 3 (2nd January 2021) - Mickiewicz, Agnieszka; Marlega, Joanna; Kuchta, Agnieszka; Bachorski, Witold; Cwiklinska, Agnieszka; Raczak, Grzegorz; Gruchala, Marcin; Fijalkowski, Marcin
Abstract: Background: Lipoprotein apheresis (LA) is a safe method of reducing atherogenic lipoproteins and improving cardiovascular (CV) outcomes. We aimed to assess the reductions in low‐density lipoprotein cholesterol (LDL‐C) and lipoprotein (a) [Lp(a)] levels in patients undergoing regular LA therapy and to evaluate its influence on the incidence rate of adverse cardiac and vascular events (ACVE) and major adverse cardiac events (MACE). Methods: A longitudinal study in Poland evaluated the prospective and retrospective observational data of 23 patients with hyperlipoproteinaemia (a) [hyper‐Lp(a)] and familial hypercholesterolemia (FH), undergoing 1014 LA sessions between 2013 and 2020. Their pre‐ and post‐apheresis LDL‐C and Lp(a) levels were assessed to calculate the acute percent reductions. The time period used to evaluate annual rates of ACVE and MACE before and after initiation of LA was matched in each patient. Results: The pre‐apheresis LDL‐C and Lp(a) concentrations were 155 (107‐228) (mg/dL) (median and interquartile range) and 0.56 (0.14‐1.37) (g/L), respectively. LA therapy resulted in a reduction of LDL‐C to 50 (30‐73.5) (mg/dL) and of Lp(a) to 0.13 (0.05‐0.34) (g/L), representing a percent reduction of 70.0% and 72.7% for LDL‐C and Lp(a), respectively. We found a significant reduction in the annual rate of ACVE (0.365[0.0‐0.585] vs (0.0[0.0‐0.265]; P = .047) and MACE (0.365[0.0‐0.585] vs 0.0[0.0‐0.265]; P = .031). Conclusions: The findings of our study indicate that LA treatment in patients with hyperlipoproteinaemia (a) and FH on maximally tolerated lipid lowering therapies leads to a substantial reduction in LDL‐C and Lp(a) concentrations and lowers CV event rates in Polish patients.